Determinants of paying national health insurance premium with mobile phone in Ghana: a cross-sectional prospective study - Joseph Marfo Boaheng; Eugenia Amporfu; Daniel Ansong; Anthony Kofi Osei-Fosu (BMC, 2019)
Abstract Introduction In an effort to increase Ghana's National Health Insurance Scheme (NHIS) enrollment and retention rates, the NHIS introduced membership renewal and premium payment by mobile phone. The success of such an innovation dependents on many factors including personal and community characteristics of members. Objective The objective of the study is to investigate the determinants of renewing membership and paying the NHIS premium through a mobile phone. Methodology The prospective cross-sectional survey was used to solicit the required information from about 1192 respondents living in Kumasi Metropolis, Atwima Nwabiaya and Sekyere Central Districts of Ghana. Logistic regression model was employed to estimate the determinants of paying the NHIS premium with the mobile phone. Results The study found that factors including residing in an urban area (Kumasi metropolis), senior high education, tertiary education and informal employees are the determinants of paying the NHIS premium with the mobile phone. Conclusion It is recommended that the NHIS consider making the mobile payment as simple as possible for the less educated and the rural members to access it.